2010
DOI: 10.1074/jbc.m110.172783
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis of the Mixed Lineage Leukemia-Menin Interaction

Abstract: Chromosomal translocations targeting the mixed lineage leukemia (MLL) gene result in MLL fusion proteins that are found in aggressive human acute leukemias. Disruption of MLL by such translocations leads to overexpression of Hox genes, resulting in a blockage of hematopoietic differentiation that ultimately leads to leukemia. Menin, which directly binds MLL, has been identified as an essential oncogenic co-factor required for the leukemogenic activity of MLL fusion proteins. Here, we characterize the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
105
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 25 publications
1
105
0
Order By: Relevance
“…We found that both MI-2 and MI-2-2 can inhibit the interaction of menin with MLL 4-43 , which comprises the intact menin-binding fragment. 19,36 As expected, the second-generation inhibitor MI-2-2 was approximately 7-fold more potent in disrupting the menin-MLL 4-43 interaction, with an IC 50 ϭ 520nM ( Figure 4A). To assess whether these inhibitors can dissociate menin interaction with the full-length MLL-AF9 fusion protein in cells, we performed coimmunoprecipitation experiments.…”
Section: Small Molecules Are Capable Of Inhibiting the Bivalent Meninmentioning
confidence: 77%
See 3 more Smart Citations
“…We found that both MI-2 and MI-2-2 can inhibit the interaction of menin with MLL 4-43 , which comprises the intact menin-binding fragment. 19,36 As expected, the second-generation inhibitor MI-2-2 was approximately 7-fold more potent in disrupting the menin-MLL 4-43 interaction, with an IC 50 ϭ 520nM ( Figure 4A). To assess whether these inhibitors can dissociate menin interaction with the full-length MLL-AF9 fusion protein in cells, we performed coimmunoprecipitation experiments.…”
Section: Small Molecules Are Capable Of Inhibiting the Bivalent Meninmentioning
confidence: 77%
“…Pro10 MLL binds to the site adjacent to Phe9 MLL and interacts with Phe238 and Ala242, whereas Pro13 MLL fits into a hydrophobic pocket formed by Tyr319, Tyr323, and Met322. Mutations of Phe9 MLL , Pro10 MLL , and Pro13 MLL to alanine residues result in a dramatic decrease of MBM1 binding to menin (2000-, 30-, and 50-fold decrease, respectively), 19 validating the importance of these hydrophobic interactions. Additional stabilization of the MBM1-menin complex results from a salt bridge between Arg12 MLL and Glu359 and Glu363, as well as 3 intermolecular hydrogen bonds involving the MLL backbone (residues Arg6 MLL , Trp7 MLL , and Ala11 MLL ) and menin side chains (Asn244, Asp136, and Tyr323; Figures 1B-C).…”
Section: Crystal Structure Of Human Menin and Menin-mll Complexmentioning
confidence: 99%
See 2 more Smart Citations
“…The last decade has witnessed many successful examples of designing smallmolecule modulators for many protein-protein interactions, including orthosteric inhibitors, allosteric regulators, and interfacial binders. Recent examples include discovering small molecule inhibitors for menin and mixed lineage leukemia (MLL) interactions [30]. Some of these molecules can inhibit the menin-MLL interaction at a nanomolar concentration [31].…”
mentioning
confidence: 99%